Carbon Dioxide-Contrasted Computed Tomography Angiography: High Pitch Protocols and Adapted Injection Parameters Improve Imaging Quality - Penzkofer, T.; Slebocki, K.; Grommes, J.; Bruners, P.; Isfort, P. P.; Heussen, N.; Schmitz-Rode, T.; Kuhl, C. K.; Langer, S.; Mahnken, A. H. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2013)
Purpose: To systematically investigate the impact of image acquisition and contrast injection parameters for CO2-enhanced CT angiography (CTA) of the aorto-iliac and peripheral arteries in a pig model using commercially available equipment. The aim was to establish an imaging protocol that is ready for use in human subjects. Materials and Methods: Three domestic swine underwent CO2-CTA with varying injection parameters: pitch (1.0, 3.0), injection pressure (0.7 bar, 1.0 bar, 1.3 bar) and scan delay (2 s, 4 s, 6 s). Objective (vessel diameter) and subjective (image quality) parameters and applied radiation doses were systematically evaluated. To ensure clinical applicability of the setting, only approved catheters/injectors and standard injection parameters were evaluated. Results: The image quality scores were superior and the vessel diameter was larger with high pitch in comparison to standard pitch (diameters: 4.7 ± 2.0 mm vs. 3.6 ± 2.1 mm, p = 0.0040, scores: 2.6 ± 1.1 vs. 2.0 ± 1.1, p = 0.0038). High injection pressure (1.3 bar) improved the image quality as assessed by subjective and objective ratings (diameters: 3.6 ± 2.0 mm, 4.0 ± 2.1 mm and 4.6 ± 2.1 mm, for 0.7, 1.0 and 1.3 bar, p-values ≤ 0.0052, scores: 1.9 ± 1.1, 2.3 ± 1.1 and 2.7 ± 1.2, p-values ≤ 0.0017), the same was observed for a shorter injection delay (diameters: 3.5 ± 2.0 mm, 4.2 ± 2.1 mm and 4.8 ± 2.1 mm, for 6 s, 4 s, and 2 s, p ≤ 0.0022, scores: 1.9 ± 1.1, 2.3 ± 1.1 and 2.7 ± 1.1, p-values ≤ 0.0013). The dose length products were 239 ± 47 mGycm (high pitch) and 565 ± 63 mGycm (standard pitch, p-values < 0.0001). Conclusion: A higher pitch, shorter delay and higher injection pressure improve image quality in CO2-enhanced CTA. Since commercially available, clinically approved equipment was used. The protocol is now ready for use in human subjects.
Keywords: CT angiography; interventional procedures; vascular; experimental